Perancangan Arduino Uno pada Design Mesin Pick and Place Sorting Colour Automation untuk Meningkatkan Produktivitas - sutita, yuwono izzah; Irwan, Heri (Universitas Muhammadiyah Surabaya Publishing, 2024)
Arduino Uno is an open-source microcontroller based on the Atmel AVR microcontroller. Arduino Uno allows users to design and develop various electronic projects easily. Arduino Uno uses an Integrated Circuit (IC), namely the ATMega328P microcontroller. Arduino Uno is designed to be easy to use even for beginners. There are many tutorials and communities ready to help. Arduino Uno is used to control the rotation of the Sg90 servo motor, and to read the color on the TCS3200 sensor, and. The purpose of this journal is to find out what components are used to control input/output and also how to write a program from the Arduino Uno. From the results of this journal, we can find out what components are used in the pick and place sorting color automation robot machine and for making machine designs. From this design, it is expected to be able to control the pick and place sorting color automation robot machine simultaneously